2017
DOI: 10.2134/agronj2016.05.0295
|View full text |Cite
|
Sign up to set email alerts
|

Sod Strength Characteristics of 51 Cool‐Season Turfgrass Mixtures

Abstract: Core Ideas Turfgrass seed mixtures containing fine fescue species can produce sod that achieves equal or greater strength than those containing large amounts of Kentucky bluegrass when harvested 22 mo after establishment. Change in proportion of fine fescues from each initial seed mixture to the resulting final plant community was negatively correlated with sod strength characteristics. Thatch development was only weakly correlated with either maximum tensile load or work required to tear sod. Mixtures with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 9 publications
3
25
0
Order By: Relevance
“…Therefore, there is a clear advantage of reduced establishment time when using sod vs. seeding. Researchers in Minnesota documented a longer fine fescue sod maturation period of 22 mo (Friell, Watkins, Horgan, & Cavanaugh, 2017); this is in comparison to a typical sod production period for Kentucky bluegrass in Minnesota of 15 mo (Friell et al., 2017), which is similar to a report of 12–20 mo in Wisconsin (Griffith et al., 2017) and 12–18 mo in both Nebraska and Maryland (Shearman et al., 2001).…”
Section: Establishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is a clear advantage of reduced establishment time when using sod vs. seeding. Researchers in Minnesota documented a longer fine fescue sod maturation period of 22 mo (Friell, Watkins, Horgan, & Cavanaugh, 2017); this is in comparison to a typical sod production period for Kentucky bluegrass in Minnesota of 15 mo (Friell et al., 2017), which is similar to a report of 12–20 mo in Wisconsin (Griffith et al., 2017) and 12–18 mo in both Nebraska and Maryland (Shearman et al., 2001).…”
Section: Establishmentmentioning
confidence: 99%
“…(2015) reported that the probability of maintaining at least 60% survival of turf after two years on Minnesota roadsides was increased when hard fescue and sheep fescue were included in seed mixtures. Further research by Friell, Watkins, and Horgan (2012, 2013, 2015, 2017) helped improve the Minnesota DOT seed mixture for low‐maintenance turf on roadsides, which now includes 29% F . rubra ssp., 20% Chewings fescue, 14% hard fescue, 11% sheep fescue, 16% low‐maintenance Kentucky bluegrass cultivars, and 10% perennial ryegrass (Minnesota DOT, 2014).…”
Section: Availabilitymentioning
confidence: 99%
“…turfgrass growth in salt-stressed conditions (Qian, Wilhelm, & Marcum, 2001 slender creeping red fescue and 40% each of hard fescue and sheep fescue has been estimated to be best suited to that environment based on results of a trial which evaluated 51 mixtures on roadsides over two years (Friell et al, 2015). Those same mixtures were subsequently grown as sod and harvested after 22 mo for tensile strength testing (Friell et al, 2017); nearly all mixtures in the top statistical grouping contained more than 90% fine fescue species in the final plant community composition. Taken together, these trials indicate that mixtures of the fine fescue species have potential for roadside establishment as both sodded and seeded mixtures (Figure 3).…”
Section: Salt Tolerance and Roadside Evaluationsmentioning
confidence: 99%
“…Furthermore, some authors have implied that the importance of Kentucky bluegrass in salt‐tolerant mixtures is likely restricted to its sod‐forming ability, which often results in higher tensile strength sod than for other species (Butler et al., 1974; Ross, Ennos, & Fitter, 1991). Still, it has been shown that the inclusion of Kentucky bluegrass in seed mixtures is not always sufficient to produce a high‐strength sod (Friell, Watkins, Horgan, & Cavanaugh, 2017).…”
Section: Review Of the Turfgrass Species Used On Roadsides In Cold Climatesmentioning
confidence: 99%
“…Using mixtures and/or blends helps account for variations in landscape microenvironments, such as sunlight availability, soil physical and chemical properties, seasonal variations in temperature, or even pest resistance. Decades of research involving turfgrass mixtures have been performed to identify which combination of species and their percentages within the mixture can improve turf quality (Hunt and Dunn, 1993;Macolino et al, 2014;Rose-Fricker et al, 1997), increase wear tolerance (Park et al, 2017;Stier et al, 2005) improve sod strength (Friell et al, 2017), enhance disease resistance (Cutulle et al, 2013), and reduce fertilizer or irrigation requirements (Dunn et al, 2002;Reiter et al, 2017).…”
mentioning
confidence: 99%